Perlindungan Hukum bagi Pemilik Hak atas Tanah dalam Penetapan Ganti Rugi Terkait dengan Pengadaan Tanah Pembangunan Jalan Tol - Zihan Tasha Maharani Fauzi; Muskibah Muskibah; Dwi Suryahartati (SENTRI: Jurnal Riset Ilmiah, 2026)
Land acquisition for public interest often generates conflicts, particularly in determining compensation for land rights holders in toll road projects. Disputes commonly arise due to differences in land valuation, procedural inconsistencies, and perceptions of fairness. One notable example is Supreme Court Decision Number 1655 K/Pdt/2024, in which the cassation appeal concerning the amount of compensation was rejected. This study analyzes the determination of the form and amount of compensation, as well as the available legal protection mechanisms. Using a normative juridical method with statutory, conceptual, and case approaches, the research finds that compensation determination has not fully complied with Article 37 of Law Number 2 of 2012. Although deliberation is required, the appraisal results are considered final and binding, creating inconsistencies and potential legal uncertainty. In Decision Number 1655 K/Pdt/2024, the Supreme Court rejected the petition because the applicant failed to provide valid legal proof of ownership and lawful transfer of land rights, particularly an authentic deed issued by a Land Deed Official (PPAT). The compensation assessment conducted by the Public Appraisal Office (KJPP) was based on officially registered data, namely the Certificate of Ownership classified as agricultural land. The Court found no misapplication of law or procedural error. This ruling reinforces the importance of formal legal documentation in compensation disputes and strengthens the principles of legal certainty and orderly land administration in land acquisition for public interest.